Fortification of γ-aminobutyric acid and bioactive compounds in Cucurbita moschata by novel two-step fermentation using Bacillus subtilis and Lactobacillus plantarum. (March 2019) - Park, Eun-Jin; Garcia, Coralia V.; Youn, Sun-Joo; Park, Chi-Deok; Lee, Sam-Pin
Abstract: Pumpkin ( Cucurbita moschata ) was co-fermented using Bacillus subtilis HA and Lactobacillus plantarum EJ2014 for producing a novel food ingredient fortified with γ-aminobutyric acid (GABA) and bioactive compounds. After the first fermentation, the broth showed pH 6.1, 0.26% acidity, 8.9 log CFU/mL viable cell counts of B. subtilis, 2.61% mucilage, and a consistency index of 5.43 Pa·s n . After the second fermentation, the broth indicated pH 5.1 and 0.23% acidity. The viable cell counts of B. subtilis decreased to 7.7 log CFU/mL, while L. plantarum counts increased from 7.4 log CFU/mL to 9.1 log CFU/mL by the end of the co-fermentation. The final mucilage content was 0.58% and consistency index was 0.15 Pa·s n . The co-fermented pumpkin contained 1.47% GABA, indicating that the MSG precursor was successfully utilized by the stepwise fermentation. Therefore, the co-fermented pumpkin paste could potentially be used as a novel ingredient for the food industry. Highlights: A fermented pumpkin-based functional ingredient was produced. Two bacterial strains were used for the co-fermentation. The co-fermented product was fortified with GABA, γ-PGA, and probiotics.